BETYdb: a yield, trait, and ecosystem service database applied to second‐generation bioenergy feedstock production. Issue 1 (7th January 2017) - LeBauer, David; Kooper, Rob; Mulrooney, Patrick; Rohde, Scott; Wang, Dan; Long, Stephen P.; Dietze, Michael C.
Abstract: Increasing demand for sustainable energy has led to research and development on the cultivation of diverse plant species for biomass production. To support the research and development required to domesticate and cultivate crops for bioenergy, we developed the Biofuel Ecophysiological Traits and Yields database (BETYdb). BETYdb is a centralized open‐access repository that facilitates organization, discovery, and exchange of information about plant traits, crop yields, and ecosystem functions. BETYdb provides user interfaces to simplify storage and discovery as well as programming interfaces that support automated and reproducible scientific workflows. Presently, BETYdb contains over forty thousand observations of plant traits, biomass yields, and ecosystem dynamics collected from the published articles and ongoing field studies. Over half of these records represent fewer than ten genera that have been intensively evaluated for biomass production, while the other half represent over two thousand plant species reflecting research on new crops, unmanaged ecosystems, and land use transitions associated with bioenergy. BETYdb has been accessed over twenty‐five thousand times and is used in the fields of bioenergy and ecosystem ecology to quantify yield potential and ecosystem functioning of crops and unmanaged systems under present and future climates. Here, we summarize the database contents and illustrate its applications. We show its utility in a new analysis that confirms that Miscanthus is twice as productive as switchgrass over a much wider range of environmental and management conditions than covered in previous analyses. We compare traits related to carbon uptake and water use of these species with each other and with two coppice shrubs, poplar and willow. These examples, along with a growing body of published research that used BETYdb, illustrate the scope of research supported through this open‐access database. Abstract : The Biofuel Ecophysiological Traits and Yields database (BETYdb) provides an open‐access repository of trait, yield, and ecosystem data in a common format. The database contains over forty thousand curated records representing crops being evaluated for biomass production as well as native vegetation. Here, we describe the database and data and present the results of two meta‐analyses: One analysis confirms that Miscanthus produces more than twice as much biomass as switchgrass under varied environments, and the second analysis compares traits related to productivity among two grasses and two coppice shrubs.